2019
DOI: 10.1186/s42047-019-0047-6
|View full text |Cite
|
Sign up to set email alerts
|

The strengths and weaknesses of gross and histopathological evaluation in hepatocellular carcinoma: a brief review

Abstract: Careful pathological analysis of hepatocellular carcinoma (HCC) specimens is essential for definitive diagnosis and patient prognostication. Tumor size and focality, gross patterns, macro-and microvascular invasion, degree of histological differentiation and expression of Keratin 19 (K19) are relevant features for risk stratification in this cancer and have been validated by multiple independent cohorts. However, there are important limitations to pathological analyses in HCC. First, liver biopsies are not rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…1 Many clinical factors are important in the prognosis of patients with HCC, including disease stage, Eastern Cooperative Oncology Group performance status (ECOG PS), histopathology, liver function and serum alphafetoprotein (AFP) levels. [2][3][4] Elevated AFP in patients with HCC is associated with worse prognosis compared with the general HCC population. [5][6][7][8][9] It has been shown that incremental changes in AFP levels (10-<100, 100-<1000 and ≥1000) at the time of HCC diagnosis are significantly associated with increased mortality independent of several demographic factors, clinical factors or treatment.…”
Section: Introductionmentioning
confidence: 99%
“…1 Many clinical factors are important in the prognosis of patients with HCC, including disease stage, Eastern Cooperative Oncology Group performance status (ECOG PS), histopathology, liver function and serum alphafetoprotein (AFP) levels. [2][3][4] Elevated AFP in patients with HCC is associated with worse prognosis compared with the general HCC population. [5][6][7][8][9] It has been shown that incremental changes in AFP levels (10-<100, 100-<1000 and ≥1000) at the time of HCC diagnosis are significantly associated with increased mortality independent of several demographic factors, clinical factors or treatment.…”
Section: Introductionmentioning
confidence: 99%
“…34–36 Likewise, the KLCA simplified HCC classification into five categories: (I) vaguely nodular, (II) expanding nodular, (III) multinodular confluent, (IV) nodular with peri-nodular extension and (V) infiltrative. 8 , 36 …”
Section: Main Findingsmentioning
confidence: 99%
“…Although trivial, it is coherent to leverage the genotype-to-phenotype sequence to support that the macroscopic appearance of HCC is unlikely random but rather reflects genomic traits of these tumors and may thus be highly contributive. 8 Gross examination may be an underestimated and underexploited source of prognostic markers in HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) (Figure 3) is a malignant hepatocellular neoplasm, commonly occurring in the setting of underlying chronic liver disease (2). Traditionally, macroscopic patterns of HCC are described as single or multiple liver nodules, massive nodules that may involve multiple liver segments, and diffuse forms with multiple small nodules throughout the liver mimicking cirrhosis (16). Tumor nodules smaller than the main tumor and less than 2 cm away (separated by non-neoplastic parenchyma) are classified as satellite nodules and usually represent intrahepatic metastases.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…Tumor nodules smaller than the main tumor and less than 2 cm away (separated by non-neoplastic parenchyma) are classified as satellite nodules and usually represent intrahepatic metastases. Nodules that are far from the primary tumor may represent either synchronous tumors or intrahepatic metastases (16). Involvement and spread through intrahepatic portal vein branches are common.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%